Gender differences in Egyptian patients hospitalized with heart failure: insights from the European Society of Cardiology Heart Failure Long‐Term Registry. (3rd September 2018) - Hassanein, Mahmoud; Abdelhamid, Magdy; Ibrahim, Bassem; Sobhy, Mohamed; Nasr, Gamela; Aboleineen, Mohamed Wafaie; Reda, Ashraf; Farag, Nabil; Elshazly, Ahmed; Abdeldayem, Tarek Khairy; Elmesseiry, Fatma; Boshra, Hesham; et al.
Abstract: Aims: This analysis evaluates gender differences in the Egyptian cohort of patients hospitalized for acute heart failure (AHF) in the European Society of Cardiology Heart Failure Long‐Term Registry. Methods and results: From April 2011 to September 2014, 1634 patients hospitalized with AHF were enrolled by 20 hospitals all over Egypt. Of these patients, 1112 (68%) patients were male and 522 (32%) were female. Women presented with a higher admission systolic blood pressure and resting heart rate. Compared with men, women had a higher body mass index (32.5 ± 9.0 vs. 29.3 ± 4.9, P < 0.001), more frequent atrial fibrillation (34.7% vs. 22.4%, P < 0.001), and anaemia defined by haemoglobin < 12 g/dL (83.1% vs. 58.4%, P < 0.001). Women were more likely to present with heart failure with preserved ejection fraction (29.7% vs. 10.6%, P < 0.001). Women had more frequent diabetes mellitus (48.1% vs. 41.6%, P < 0.05) and hypertension (48.7% vs. 39.3%, P < 0.001) than had men, whereas smoking was rare among them (8.8% vs. 82.9%, P < 0.005). There was no significant difference in the primary aetiology of heart failure between both sexes. ACE inhibitors, beta‐blockers, mineralocorticoid receptor antagonists, antiplatelets, statins, and nitrates were less frequently prescribed to women, whereas they more often received digoxin, amiodarone, anticoagulants, and calcium channel blockers. There was no significant difference in in‐hospital (5.7% vs. 4.6%, P = 0.39) and 1 year mortality (27.9% vs. 25.9%, P = 0.48) between women and men, respectively. Conclusions: Men and women with AHF differ significantly in baseline clinical characteristics and management but not in adverse outcomes. These findings emphasize the importance of individualized management and need for more comprehensive recruitment of women in clinical trials.